X-linked Recessive Distal Myopathy With Hypertrophic Cardiomyopathy Caused by a Novel Mutation in the FHL1 Gene. (August 2015) - D'Arcy, Colleen; Kanellakis, Voula; Forbes, Robin; Wilding, Brendan; McGrath, Meagan; Howell, Katherine; Ryan, Monique; McLean, Catriona
FHL1 gene mutations are associated with reducing body myopathy, X-linked myopathy with postural muscle atrophy, scapuloperoneal myopathy, Emery-Dreifuss muscular dystrophy, and isolated hypertrophic cardiomyopathy. We describe a boy with a family history consistent with X-linked distal myopathy/cardiomyopathy. The boy first presented at age 14 years and was found to have distal wasting and weakness. Echocardiogram revealed hypertrophic cardiomyopathy. Muscle biopsy showed a vacuolar pathology with no reducing bodies. Sequencing of FHL1 revealed a novel hemizygous c.764G>C missense mutation in exon 8. This is the first report of a predominantly distal myopathy with hypertrophic cardiomyopathy occurring secondary to an FHL1 mutation.